Eastern and western perspectives : papers from the 1978 Joint Atlantic Canada/Western Canadian Studies Conference - Bercuson, David Jay; Buckner, Phillip A. (Phillip Alfred), 1942- (Western Canadian Studies Conference, 1981)
The Atlantic Canada and Western Canada Studies Conferences have focused attention in recent years on the culture and development of two widely separated regions which have been frequently ignored in studies of the Canadian nation. The Atlantic Canada Studies Conference, meeting in 1974 and 1976 at the University of New Brunswick, and the Western Canadian Studies Conference, meeting annually since 1968 at the University of Calgary, have brought together scholars from a variety of disciplines to study the identities and characteristics of these two hinterlands. In 1978 the two conferences met jointly, in a session in Fredericton and one at Calgary with a core of speakers and papers common to both. The purpose was to compare and contrast subjects and experiences of interest and concern in the west and in Atlantic Canada. The ten papers which comprise Eastern and Western Perspectives are selected from twenty-seven presented at the joint conference. The topic chosen not only illustrate some of the preoccupations of regional historians and political scientists, but also echo many of the concerns of Canadians in general. The plight of islands and francophone culture in the midst of an overwhelmingly Anglo-American society, the search for identities in the face of persisting stereotypes, the effects of economic and urban development, the distinctiveness of local political cultures--all are subjects whose study enriches both regional and national history. This volume brings together explorations of these themes from eastern and western points of view and makes a unique contribution to a greater understanding and awareness of the regional dimension in Canadian life.